COMPARISON STUDY IN USING PLOUGH, TRACTOR AND CULTIVATOR FOR RICE FIELD’ LAND PREPARATION - Sutjana, I.D.P.; Adiputra, I Nyoman (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2008)
Land preparation of the rice field is one of the most important steps for paddyplantation. Formerly plough is one of the main tools for land preparation, but now thefarmer used tractor or cultivator. From the farmer experience who are used that tools forland preparation there had advantages and disadvantages. The used of plough for landpreparation for long time ago the deep of rice field soil is constant because the ploughblade can be adjusted up and down. The plough can be turn to the right or left side so thatall part of rice field except the corner can be cultivate. But for pulling the plough must bedifficult to find two cows. While if using tractor or cultivator the right or left side and thecorner of the rice field can’t be cultivate. Deep of rice filed soil become shallow so thefertility of soil reduced. Beside that using tractor or cultivator for land preparation needmore fuel. The plough were easy to carry out, but tractor and cultivator difficult to carryout because the weight more that 200 kg.